New insights into therapeutic activity and anticancer properties of curcumin - Panda AK; Chakraborty D; Sarkar I; Khan T; Sa G (Dove Medical Press, 2017)
Abir Kumar Panda, Dwaipayan Chakraborty, Irene Sarkar, Tila Khan, Gaurisankar Sa Division of Molecular Medicine, Bose Institute, Kolkata, West Bengal, India Abstract: Natural compounds obtained from plants are capable of garnering considerable attention from the scientific community, primarily due to their ability to check and prevent the onset and progress of cancer. These natural compounds are primarily used due to their nontoxic nature and the fewer side effects they cause compared to chemotherapeutic drugs. Furthermore, such natural products perform even better when given as an adjuvant along with traditional chemotherapeutic drugs, thereby enhancing the potential of chemotherapeutics and simultaneously reducing their undesired side effects. Curcumin, a naturally occurring polyphenol compound found in the plant Curcuma longa, is used as an Indian spice. It regulates not only the various pathways of the immune system, cell cycle checkpoints, apoptosis, and antioxidant response but also numerous intracellular targets, including pathways and protein molecules controlling tumor progression. Many recent studies conducted by major research groups around the globe suggest the use of curcumin as a chemopreventive adjuvant molecule to maximize and minimize the desired effects and side effects of chemotherapeutic drugs. However, low bioavailability of a curcumin molecule is the primary challenge encountered in adjuvant therapy. This review explores different therapeutic interactions of curcumin along with its targeted pathways and molecules that are involved in the regulation of onset and progression of different types of cancers, cancer treatment, and the strategies to overcome bioavailability issues and new targets of curcumin in the ever-growing field of cancer. Keywords: apoptosis, cancer, cell signaling, combinatorial therapy, curcumin/nanocurcumin, drug resistance